Parole as resentencing: Exploring the punitive accounts of parole decision-making through the comparative case study of Israel - Dagan, Netanel (European journal of criminology, 2023)
Parole boards have traditionally assessed prisoners? future risk and rehabilitation prospects in deciding on early release from prison. However, parole boards may do more. In some systems, they may deny parole applications for punitive reasons, thus acting as a resentencing authority. This study conducted a qualitative analysis of the punitive discourses of parole decision-making, with Israel as a comparative case study. Through interviews with 20 chairpersons of Israeli Parole Boards, we found three themes of punitive parole decision-making: (a) preserving public confidence in the criminal justice system; (b) preserving penal proportionality; and (c) re-censuring an especially depraved moral character. The findings suggested that parole boards? punitive discretion is multidimensional and complex. Such punitive discretion may be openly implemented, it may be cloaked as risk assessment, or decided without formal recognition. The findings further indicated that resentencing through discretionary parole may not only conflict with rehabilitation and risk aims, but may also raise challenges for retributive and deterrent penal policy. Implications for comparative parole policy are discussed.